2017
DOI: 10.1155/2017/9161025
|View full text |Cite
|
Sign up to set email alerts
|

Damage Identification of Unreinforced Masonry Panels Using Vibration-Based Techniques

Abstract: Several damage indicators based on changes in modal properties validated for homogeneous materials were applied to detect damage in an unreinforced masonry cantilever panel. Damage was created by a "clean diagonal cut" at the center of the specimen which length was progressively extended towards the specimen's corners. Numerical simulations were employed to determine the modal response at several damage states and this data was used to calculate the damage indicators. Those indicators presenting a good perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Young's modulus and/or shear modulus or, alternatively, local increases in the wavenumbers of the propagating pulses in virtue of Eqs. ( 17) and (18). Similar assumptions are common in damage identification techniques via computational model updating, being suitable for early-stage damage where the structure can be hypothesized to remain elastic.…”
Section: Visco-elastic Layered Timoshenko Beam Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Young's modulus and/or shear modulus or, alternatively, local increases in the wavenumbers of the propagating pulses in virtue of Eqs. ( 17) and (18). Similar assumptions are common in damage identification techniques via computational model updating, being suitable for early-stage damage where the structure can be hypothesized to remain elastic.…”
Section: Visco-elastic Layered Timoshenko Beam Modelmentioning
confidence: 96%
“…A large number of output-only algorithms can be found in the literature, including among others Eigensystem Realization Algorithm (ERA) [12], Natural Excitation Technique (NExT) [13], Stochastic Subspace Identification (SSI) [14], Frequency Domain Decomposition (FDD) [15], or Blind Source Separation (BSS) [16]. In this light, these techniques offer solutions for condition monitoring that are physically based on detecting damage-induced changes in the identified modal features [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Tests on the infill are performed before and after the application of the blast loads; however, the mode shapes identified in both cases are not comparable with those of a typical plate element. Boscato et al [118] and Oyarzo-Vera and Chouw [119] performed AVTs and ILTs, respectively, on masonry wall laboratory specimens with the aim of identifying their OOP dynamics. Data from these interesting works are not considered in this paper because the specimens are built following the masonry building construction materials and techniques, hence they are not representative of masonry infills in RC frame buildings.…”
Section: Dynamic Tests On Infill Masonry Wallsmentioning
confidence: 99%
“…Recently, structural health monitoring methods based on structural global vibration were widely accepted both in academic community and engineering community. For example, Oyarzo-Vera and Chouw [3] conducted damage identification of unreinforced masonry panels using vibration-based techniques, and the outcomes demonstrated that vibration-based damage detection in unreinforced masonry structures can be satisfactorily performed. Dynamic parameters such as natural frequency, damping ratio, modal shape, strain mode shape, modal strain energy, and flexibility matrix were fully developed for damage detection.…”
Section: Introductionmentioning
confidence: 99%